CASE REPORT ON PARATHYROID CARCINOMA: THE RISK OF LOCOREGIONAL DISEASE PROGRESSION AND THE ROLE OF RADIATION AND MEDICAL THERAPY POST-OPERATIVELY - Romina, Kristiana Margarette (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Parathyroid carcinoma is an extremely rare endocrine neoplasm, accounting for less than 1% of patients with primary hyperparathyroidism. The infrequency of this disease poses a challenge to the clinician as to the appropriate management after surgical resection. We present the case of a 63-year-old Filipino female with primary hyperparathyroidism, multinodular goiter and chronic kidney disease stage 4 who underwent total thyroidectomy with excision of a parathyroid mass. Pathological diagnosis revealed a 3-cm and 2.8-cm multifocal GATA3-positive parathyroid carcinoma with capsule invasion. Adjuvant radiation therapy was offered but the patient opted for observation and close monitoring. Eight months postoperatively, her calcium and intact parathyroid hormone levels were normal without the need for bisphosphonates, calcimimetics or denosumab. In this report, we review the risk for loco-regional disease progression and the role of radiation and medical therapy in the post-operative care of patients with parathyroid carcinoma.